The role of cell proliferation and crypt fission in adenoma aggressiveness: a comparison of ileoanal pouch and rectal adenomas in familial adenomatous polyposis. - Will, O; Deheragoda, M; Phillips, R; Clark, S; Tomlinson, I (2011)
AIM: In patients with familial adenomatous polyposis (FAP), ileoanal pouch cancer is rare whereas rectal cancer is common, despite polyp initiation at the two sites being similar at the molecular level. This study investigated whether the disparity in adenoma aggressiveness reflects underlying differences in histogenesis. METHOD: Normal mucosal biopsies and 2-3 mm adenomas from patients with FAP were dissected into individual crypts. Crypt area, morphology, fission and mitoses were analysed for crypts from pouch, rectum and supra-anastomotic ileum. Immunohistochemistry of similar archival samples was performed for lysozyme, β-catenin and TP53 expression. RESULTS: The morphology of normal crypts was similar at each site, although crypt area differed. The area of normal pouch crypts was intermediate between rectum and ileum. The area of adenomatous crypts of rectum and pouch was similar, but the latter had increased asymmetrical fission. Crypt mitoses were proportional to area in all tissues, but crypt fission was reduced in adenomatous crypts from the rectum compared with the pouch. Pouch adenomas retained lysozyme expression as seen in normal ileum. Nuclear β-catenin accumulation was similar, but TP53 expression was increased in rectal adenomas. CONCLUSION: Diminutive polyps from rectum and pouch differ in morphology and proliferation. Aggressiveness in rectal polyps is not conferred by increased crypt proliferation, fission, or activation of the Wnt signalling pathway. Increased TP53 expression suggests other molecular mechanisms may be responsible. While crypt mitoses are proportional to crypt area, the threshold for fission may be site specific, indicating that tissue origin may influence histogenesis and thus malignant potential.